Sociocultural experiences, body image, and indoor tanning among young adult women. (October 2017) - Stapleton, Jerod L; Manne, Sharon L; Greene, Kathryn; Darabos, Katie; Carpenter, Amanda; Hudson, Shawna V; Coups, Elliot J
The purpose of this survey study was to evaluate a model of body image influences on indoor tanning behavior. Participants were 823 young adult women recruited from a probability-based web panel in the United States. Consistent with our hypothesized model, tanning-related sociocultural experiences were indirectly associated with lifetime indoor tanning use and intentions to tan as mediated through tan surveillance and tan dissatisfaction. Findings suggest the need for targeting body image constructs as mechanisms of behavior change in indoor tanning behavioral interventions.